The basic criteria for the provision of affordable housing in Melaka - Mohamed Osman, Mariana; Ramlee, Muhammad Adib; Ab Rahman, Syakir Amir; Ibrahim, Mansor (2017)
The aim of this paper is to examine the criteria considered in the selection of the houses by the homebuyers in Melaka. The case study area that has been selected is in the state of Melaka and this is also supported by the report produced by Khazanah Research Institutes (KRI) in 2015 that claimed Melaka is the most affordable state in Malaysia. The study applies the quantitative approach, the Yamane Taro 1976 formula is used and 400 samples are selected. In addition the random sampling methods has been using in sample selection and three types of analysis techniques have been used such as descriptive analysis, Pierson correlation and Relative Importance Index (RII). The study found that the three districts in Melaka are at affordable range for 2012 and 2014 and the income level of the household in Melaka is within the average income of Malaysia. Finally it is hoped the study will help to give a clear picture on what are main criteria that should be provided in provision a better housing provision in Malaysia.